2016
DOI: 10.4028/www.scientific.net/amr.1133.108
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Effects by Genipin on Physicochemical Properties of Chitosan Film

Abstract: The aim of this paper was to investigate the effects of cross-linked reaction on physicochemical properties of chitosan film by using genipin as cross-linker agent. Series of chitosan film samples with different amount concentration of genipin loaded (0-3 wt %) were prepared and characterized. The physicochemical properties of films were evaluated by Fourier Transform Infra-red (FTIR), UV-vis spectroscopy, Oxygen Transmission Rate (OTR), Scanning Electron Microscopy (SEM), water vapour and tensile test. The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…These were probably caused by the crosslink occurring between the amino groups of chitosan and the olefinic carbon atom at C-3 of genipin (Dimida et al, 2015;Pomari et al, 2019). Moreover, a band located at 1442 cm −1 in genipin associated with carboxymethyl groups in genipin had disappeared in the crosslinked film, suggesting there were crosslinks between amino groups in chitosan and carboxymethyl groups in genipin (Hisham et al, 2016) The shifted vibration of the absorption bands at 1716 and 1568 cm −1 of CS-25 and 1718 and 1570 cm −1 of CSA-25 was observed when curing temperature increased. Moreover, the appearance of a new peak at 1410 cm −1 was detected for CAG after cured at 80 and 105 °C, which probably indicated C-C bridges between genipin and genipin (Vlȃsceanu et al, 2020) as shown in Fig.…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These were probably caused by the crosslink occurring between the amino groups of chitosan and the olefinic carbon atom at C-3 of genipin (Dimida et al, 2015;Pomari et al, 2019). Moreover, a band located at 1442 cm −1 in genipin associated with carboxymethyl groups in genipin had disappeared in the crosslinked film, suggesting there were crosslinks between amino groups in chitosan and carboxymethyl groups in genipin (Hisham et al, 2016) The shifted vibration of the absorption bands at 1716 and 1568 cm −1 of CS-25 and 1718 and 1570 cm −1 of CSA-25 was observed when curing temperature increased. Moreover, the appearance of a new peak at 1410 cm −1 was detected for CAG after cured at 80 and 105 °C, which probably indicated C-C bridges between genipin and genipin (Vlȃsceanu et al, 2020) as shown in Fig.…”
Section: Ftir Analysismentioning
confidence: 99%
“…Genipin isolated from Gardenia is accepted as an alternative crosslinking agent owing to non‐toxicity, and thus can be applied as an effective natural crosslinking agent for biopolymers containing amino groups, especially chitosan. Several studies have reported that genipin as crosslinker can improve functional properties of chitosan film (Hisham et al ., 2016; Kildeeva et al ., 2020). Our previous study has reported that genipin crosslinker can improve physical, moisture barrier and mechanical properties of chitosan–astaxanthin film to a moderate extent (Inthamat et al ., 2021), but the certain functional properties, especially high moisture barrier and strong mechanical properties necessary for high moisture food application, have not been conclusively established and thus required further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CSGTA, infrared (IR) peaks were observed at 1564 and 1414 cm −1 , corresponding to C=N (stretch) of the imine bond and C–H (bending) between the aldehyde group of GTA and primary amine in CS due to a nucleophilic addition reaction [ 14 , 22 ]. Likewise, the CSGP showed peaks at 1656, 1564, and 1415 cm −1 , corresponding to C=O (stretch)/N–H (bending) of the amide bond and C–H (bending) of the methyl ester group in GP, respectively [ 19 , 23 ]. However, using only FT-IR spectra to confirm the crosslinking reaction of CSCA, CSGTA, and CSGP films was difficult and insufficient because their IR peaks overlapped with those of the primary amine and newly formed amide bonding of neat and crosslinked CS.…”
Section: Resultsmentioning
confidence: 99%
“…Although the interaction between the CS chains becomes strong because of the good crosslinking reaction efficiency with increased crosslinker concentrations, the films exhibited brittle properties. These results mean that the mobility of the CS interchain in the CSGTA and CSGP films was more restricted by the crosslinking reactions [ 16 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation